Echocardiographic Patterns in Severe Chronic Kidney Disease with Type 4 Cardiorenal Syndrome Patients - Ghose, Rajesh Kumar; Karim, Md Rezaul; Hoque, Harisul; Mondol, Rais Uddin; Ghosh, Rita (TAJ: Journal of Teachers Association, 2022)
Changes in cardiac structure and function detected by echocardiography are common in patients with type 4 cardiorenal syndrome and have been recognized as key outcome predictors. This study aimed to evaluate echocardiographic patterns in severe chronic kidney disease CKD in type 4 cardiorenal syndrome patients. This was a descriptive type of cross-sectional study. The study was carried out in the Cardiology and Nephrology Department of Bangabandhu Sheikh Mujib Medical University, Dhaka. After exclusion total of 44 patients having severe CKD (GFR <30 ml/min/1.73 m2) with type 4 cardiorenal syndrome were included in this study. All patients underwent echocardiography. Most of the patients with type 4 cardiorenal syndrome were in the 6th decade (Mean age was 58.9±5.9 (SD)in severe CKD with male predominant. Ischemic heart disease(65.9%), arrhythmia(13.63%), and heart failure(22.72%) were significantly noted in severe CKD in type 4 cardiorenal syndrome patients. Mean systolic blood pressure was 178.2±18.7 mmHg & mean diastolic blood was 97.7±5.9 mmHg among the study subjects. Left ventricular hypertrophy (54.6%), systolic dysfunction (27.3%), pericardial effusion (36.4%), valvular calcification (63.6%), and diastolic dysfunction (54.5%) were most common finding in severe CKD with type 4 cardiorenal syndrome. The study recommended that a Careful analysis of echocardiographic findings in patients with type 4 cardiorenal syndrome may discover the signs of cardiovascular changes. Thus appropriate measures can be taken. From this current study, it is evident that most of the patients with type 4 CRS with severe CKD developed left ventricular hypertrophy, so periodic 24-hour ambulatory blood pressure monitoring may be advised to address the unusual rise of blood pressure and treat it properly. TAJ 2022; 35: No-1: 11-16